2016
DOI: 10.1111/psyg.12188
|View full text |Cite
|
Sign up to set email alerts
|

Changes in job stress and coping skills among caregivers after dementia care practitioner training

Abstract: The findings suggest that training caregivers improves their stress reaction and coping skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Table 2 summarizes basic characteristics of all 55 relevant studies in 60 articles [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99] selected in our review, with a consolidated description of this material following.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes basic characteristics of all 55 relevant studies in 60 articles [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99] selected in our review, with a consolidated description of this material following.…”
Section: Resultsmentioning
confidence: 99%
“…It also highlights the need for formal caregiver training, a desire strongly expressed by caregivers of every injury. Caregiver training has been demonstrated to improve caregiver self-efficacy and stress management [31-33]. Comprehensive health care systems should therefore incorporate structured training programs to reduce caregiver burnout and dependence on medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the results of studies on training interventions for burnout have been inconclusive thus far. Some studies have reported decreased burnout after training interventions, 24,25,31 whereas others have found no change. 27,32 However, the type of intervention seems to determine the results.…”
Section: Discussionmentioning
confidence: 99%
“…22 The literature includes numerous studies on interventions to prevent or decrease burnout in elder care nursing staff. 13,19 Some studies on training interventions address the importance of training in helping caregivers cope with the difficulties and challenges of caring for persons with dementia, [23][24][25][26] but others suggest that training is ineffective. 27 However, most agree that more studies are needed to evaluate the effectiveness of training and other interventions in preventing burnout.…”
Section: Introductionmentioning
confidence: 99%